Zoning code of Social Housing in Metropolitan Lima: Exclusionary zoning and infringement of the right to housing - Devoto Ykeho, Andres (2023)
The objective of this article is to analyze the role of urban planning and building parameters in guaranteeing the right to adequate housing in Metropolitan Lima, with emphasis on social housing (SIV). To this end, we develop a state of the art on the urban regulation of SIV until December 2022, which shows that there is no consensus among the different levels of government regarding the mechanisms to promote the production of SIV and guarantee the right to housing. Then, we analyze the impact of urban and building parameters on the right to housing and other legal rights and goods.Based on this analysis, we present two arguments.First, we argue that the urban and building parameters approved by the municipalities of Metropolitan Lima represent a case of exclusionary zoning, as they limit or prohibit the production of SIV in areas with greater access to services and facilities. The second argument is that the incentives of the Special Regulation –i.e., the table of SIV parameters– do not guarantee the right to housing because they do not ensure adequate access to services and facilities for SIV beneficiaries.